Comparative Techno-Economic Evaluation of LTE Fixed Wireless Access and FTTdp G.fast network deployment for providing broadband services of at least 30Mbps in rural areas - Nikos Ioannou; Dimitris Katsianis; Dimitris Varoutas (International Telecommunications Society (ITS), 2018)
In rural areas in Europe, the deployment of High-Speed Broadband access networks lags behind in urban and suburban areas due to difficulties of deployment of fiber in the final meters. FTTdp networks using G.fast have been proposed as a cost-effective alternative to FTTH and FTTB [1] especially in rural areas [2] where FTTC and VDSL cannot always deliver service speeds of 30Mbps which is the minimum bandwidth defined in the European Digital Agenda as target to be met by 2020. However, fixed wireless access (FWA) networks based on LTE technology can be used as a "last mile" solution to provide high-speed broadband access to areas where fixed broadband is limited [3]–[5]. On the other hand, LTE technology offers high speed connections able to support internet browsing and IP services, while it can theoretically support up to 300 Mbps depending on network load and sharing. Thus, it can be considered as a true alternative to any fixed solution. In this paper, a techno-economic study is performed to assess the feasibility of a FWA network deployment based on LTE technology in comparison to FTTdp G.fast network rollout for delivering service speeds of 30Mbps in rural areas. We present cash flow results and standard financial indexes for the business cases discussed. The results are being appraised through a sensitivity and risk analysis to determine the most influential factors on the return on the investment. We also discuss the (non) profitability of both cases and the subsidization needed from structural funds. The results aim to contribute in the debate over network evolution scenarios among academia, industry, regulators, policy makers and governments.
Keywords: 330; Techno-economic; NPV; LTE; G.fast; FWA; FTTdp; FTTx; digital agenda; subsidization; NGA; Broadband